2019
DOI: 10.3390/s19153420
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Estimation from Photoplethysmogram Using a Spectro-Temporal Deep Neural Network

Abstract: Blood pressure (BP) is a direct indicator of hypertension, a dangerous and potentially deadly condition. Regular monitoring of BP is thus important, but many people have aversion towards cuff-based devices, and their limitation is that they can only be used at rest. Using just a photoplethysmogram (PPG) to estimate BP is a potential solution investigated in our study. We analyzed the MIMIC III database for high-quality PPG and arterial BP waveforms, resulting in over 700 h of signals after preprocessing, belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
202
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(239 citation statements)
references
References 24 publications
(36 reference statements)
4
202
2
4
Order By: Relevance
“…The voltage change of SBP and DBP feature points within adjacent PPW signals can be acquired, according to Equations (8) and (9). The pressure sensitivity of the piezoelectric sensor offers a unit conversion of 2 mmV/mmHg that implies that the pressure change is 0.5 mmHg per mV, according to Equation (10). Therefore, the pressure change of SBP and DBP feature points between the adjacent PPW signals were obtained by (11).…”
Section: Post-processing Unitmentioning
confidence: 99%
See 2 more Smart Citations
“…The voltage change of SBP and DBP feature points within adjacent PPW signals can be acquired, according to Equations (8) and (9). The pressure sensitivity of the piezoelectric sensor offers a unit conversion of 2 mmV/mmHg that implies that the pressure change is 0.5 mmHg per mV, according to Equation (10). Therefore, the pressure change of SBP and DBP feature points between the adjacent PPW signals were obtained by (11).…”
Section: Post-processing Unitmentioning
confidence: 99%
“…The experimental results indicated that the MAE ± SD for SBP and DBP were validated by a sphygmomanometer, and obtained 1.52 ± 9.45 mmHg and 0.39 ± 4.93 mmHg on 44 subjects. Slapniˇcar et al [10] created a blood pressure estimation model by PPG measurement and deep neural network. The results obtained MAE for SBP and DBP were, respectively, 9.43 and 6.88.…”
Section: Accuracy Evaluation With Other Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, ECG and PPG signals are widely used for the evaluation of cardiovascular function. Characteristics of PPG waveforms such as amplitude, peak-peak time, and dicrotic notch were used for blood pressure estimation [23][24][25][26][27], hypertension assessment [28], and cardiovascular risk evaluation [29]. Since noise-free signals are very important when using the feature points of a biosignal, silicon photomultipliers (SiPMs) were adopted instead of the conventional photodiode (PD) [30] to obtain clear PPG waveforms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been some progress in the utilisation of deep learning techniques for the prediction of BP [29][30][31][32][33]. Su et al [30] devised a multi-layer recurrent neural network (RNN) network named DeepRNN and multi-task training strategy is utilized to train a model to predict systolic BP(SBP), diastolic BP(DBP) and mean BP(MBP) simultaneously.…”
Section: Introductionmentioning
confidence: 99%